Response to Mesalamine Therapy in Pediatric Collagenous Gastritis and Colitis: A Case Report and Review - Ankit Mishra MS; Joon Chung BS; Haresh Mani MD; Mariastella Serrano MD, FAAP (SAGE Publishing, 2022)
Collagenous gastritis and collagenous colitis are 2 rare gastrointestinal disorders in pediatric patients. Both of these disease processes exist on a clinical spectrum, and are extremely rare to be present together in the pediatric population. Due to the rarity and unknown etiology of these disease processes, standardized treatment protocols and objective clinical biomarkers of disease progression are missing. This is the first report to describe a 16 year old female with CG and CC who responded well to mesalamine therapy, evident by decreasing calprotectin levels after initiation of therapy.